An Ecological Approach to Psychology. Issue 2 (June 2013) - Heft, Harry
Even though the term "ecology" was introduced into scientific discourse in the 1860s, and by century's end much of experimental psychology had embraced an evolutionary perspective, it took more than another half century before proposals for an ecological psychology began to appear. Even so, ecological psychology was marginalized from the mainstream of the discipline, and it remains so today. This disjunction between psychology's embrace of evolutionary theory and its resistance to ecological thinking can be explained, in large part, historically. It was Herbert Spencer's evolutionary framework, that assumes an environment-mind dichotomy, which was embraced by most early psychologists, and its influence remains today. A Darwinian perspective, in contrast, stresses the activity of an organism in the context of the dynamic mutual relations of its econiche. At the heart of Darwinian thinking, and in turn ecological psychology, are dynamic organism-environment relations, functionally meaningful environmental properties, as well as change and variation. An ecological psychology also recognizes that humans, like other living things, adapt to their econiche, in part, by altering it and thereby modifying the econiche's functional properties. The human econiche, in particular, is characterized by functionally significant, socially normative meanings owing to the sociocultural systems that naturally stem from the character of hominid evolution.